Perilaku Remaja Putri dalam Pembelian Produk Hijau "The Body Shop" di Kota Denpasar - Trikrisna, Arieta Sara; Rahyuda, I Ketut (E-Jurnal Manajemen; Vol 3 No 7 (2014), 2014)
The purpose of this research was to determine the peer influence and environmental knowledge on environmental attitude, and the influence of environmental attitude on green product purchasing behavior, as well as to find out the attitude and behavior diversity of "The Body Shop" adolescent girl consumers in Denpasar based on time to purchase products. Probability Proportionate to Zise sampling technique used in this research and take 104 people as final sample. The results of SEM and multiple group analysis, showed that peer influence and environmental knowledge significantly has positive effect on environmental attitude, and environmental attitude significantly has positive effect on green product purchasing behavior. But from two groups examined based on time to purchase products, showed that all variables significantly have positive effect, except peer influence variable discovered not significantly has positive effect to environmental attitude of respondents group who purchase the product in the morning till noon. Keyword: peer influence, environmental knowledge, environmental attitude, green product purchasing behavior, adolescent girl consumers